Literature review of visual representation of the results of benefit–risk assessments of medicinal products†. Issue 3 (2nd November 2015) - Hallgreen, Christine E.; Mt‐Isa, Shahrul; Lieftucht, Alfons; Phillips, Lawrence D.; Hughes, Diana; Talbot, Susan; Asiimwe, Alex; Downey, Gerald; Genov, Georgy; Hermann, Richard; Noel, Rebecca; Peters, Ruth; et al.
Abstract: Background: The PROTECT Benefit–Risk group is dedicated to research in methods for continuous benefit–risk monitoring of medicines, including the presentation of the results, with a particular emphasis on graphical methods. Methods: A comprehensive review was performed to identify visuals used for medical risk and benefit–risk communication. The identified visual displays were grouped into visual types, and each visual type was appraised based on five criteria: intended audience, intended message, knowledge required to understand the visual, unintentional messages that may be derived from the visual and missing information that may be needed to understand the visual. Results: Sixty‐six examples of visual formats were identified from the literature and classified into 14 visual types. We found that there is not one single visual format that is consistently superior to others for the communication of benefit–risk information. In addition, we found that most of the drawbacks found in the visual formats could be considered general to visual communication, although some appear more relevant to specific formats and should be considered when creating visuals for different audiences depending on the exact message to be communicated. Conclusion: We have arrived at recommendations for the use of visual displays for benefit–risk communication. The recommendation refers to the creation of visuals. We outline four criteria to determine audience–visual compatibility and consider these to be a key task in creating any visual. Next we propose specific visual formats of interest, to be explored further for their ability to address nine different types of benefit–risk analysis information. Copyright © 2015 John Wiley & Sons, Ltd.